2021
DOI: 10.25046/aj060221
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic and Commodities Prices on Booking.com Share Price

Abstract: This paper examines the impacts of the COVID-19 pandemic and selected commodity variables on Booking.com share price using the Markov-switching approach. Daily data spans from January 2017 through July 2020 are utilized in this study. Empirical evidence showed that COVID-19, international crude oil price, and gold price affected the Booking.com share price significantly. A positive relationship was detected between international crude oil price and gold price towards stock price whereas COVID-19 showed an inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The long-run influence of oil prices on selected indexes is positive due to Malaysia's oil-export-based economy. The findings of the current study corroborate the claim of Jong et al (2021) that variations in international crude oil prices put a substantial impact on various areas of the financial sector, particularly on the stock market. This study observed the intensity of the lead-lag association between oil and prices of stock differs at the different frequency levels.…”
Section: Frontiers In Energy Researchsupporting
confidence: 86%
“…The long-run influence of oil prices on selected indexes is positive due to Malaysia's oil-export-based economy. The findings of the current study corroborate the claim of Jong et al (2021) that variations in international crude oil prices put a substantial impact on various areas of the financial sector, particularly on the stock market. This study observed the intensity of the lead-lag association between oil and prices of stock differs at the different frequency levels.…”
Section: Frontiers In Energy Researchsupporting
confidence: 86%
“…According to the Bureau of Labor Statistics (BLS), producer price index (PPI) monitors the average changes over time in market selling prices. The index is a combination of products and services prices from the first commercial transaction (Jong et al, 2021). Our empirical findings showed that LPPI and LTA have a negative relationship during recession and a positive relationship during growth period.…”
Section: Resultsmentioning
confidence: 67%
“…The mobility of the people fell sharply due to the quarantine regulations by the government which caused the country's economy to become weaker. In the business world, Covid 19 has affected the stock market (Jong et al, 2021;Muttaqien & Sulistyan, 2022;Yatminiwati et al, 2021). Covid 19 affects the movement of the rupiah exchange rate and the stock price index (Shen et al, 2020;Cahyaningati et al, 2022;Sulistyan et al, 2022), Covid 19 also affects the performance of energy industry companies , property companies (Roosdiana, 2020), affects the performance of companies in Indonesia, China (Jong et al, 2021) and Pakistan.…”
Section: Introductionmentioning
confidence: 99%